THE SHERLOCK HOLMES ENCYCLOPEDIA - Bunson, Matthew E., author 640823 (London : Pavilion Books Limited, 1995)
This reference book sets out to capture the life and times of Sherlock Holmes. Over 1500 entries are arranged alphabetically, providing synopses of every case in the stories and novels. Included are profiles of notable figures and descriptions of the real cases which inspired Conan Doyle.